SOURCES OF BIAS IN SELF-ASSESSED HEALTH - C. J. Gerry; V. M. Baydin (IRBIS LLC, 2018)
Self-assessed health (SAH) is a widely used measure in public health research. The World Health Organization in 1996 recommended the use of SAH as one of the main indicators for monitoring the health and quality of life of the population. However, SAH is a subjective indicator and subject to bias stemming from individual characteristics and external factors. In this review paper, we classify self-reported health and the sources of potential bias in this measure which must be considered by academic researchers as well as in the evaluation and comparison of these indicators.